Análise dos níveis de metais potencialmente tóxicos e análise microbiológica nas águas da bacia do Educandos (Manaus - AM) - Silva, Mauricio Brito da (2010)
This work aimed to verify by physical-chemical and microbiological commitment basin Pupils due to inadequate release of waste (liquid and solid) from domestic sewage and industrial waste. Accordingly, water samples in various parts of the basin were collected, using as a criterion for the rainy season period (May/2009) and dry (out/2009) at 25 sites along the basin of Pupils. In the water samples were determined for pH, electrical conductivity and the concentration of Cu, Cd, Cr, Co, Hg, Zn, Pb and Ni. The pH and electrical conductivity were obtained in the field, and metals by atomic absorption spectrometry flame air / acetylene and hydride generator. Microbiological analysis, the results showed high levels of fecal coliform in the collection points analyzed. The results show that in the dry season the water pollution problems become more evident, especially at points close to dumping of industrial effluents and domestic sewage. In these regions the values found exceed those permitted by CONAMA, for example, exists in the waters far above the amount of coliform 1000. Keywords: environmental microbiology, domestic sewage, industrial effluent, heavy metal, FAAS.